INFLUENCE OF TRANSPORT OPERATIONS ON THE CHANGING LOCAL CLIMATE IN NIGERIA’S SOUTHWESTERN CITIES - Umar Obafemi SALISU; Simeon Oluwagbenga FASINA; Hazzan Tunde SHODUNKE; Ayobami Ademola AKANMU; Sekinat Motunrayo SANNI; Samuel Oluwaseyi OLORUNFEMI (Scientific Journal of Silesian University of Technology. Series Transport)
The activities of transport operations exhibit both positive and negative outcomes. Its negative effects on human health and the sustainability of the environment are of interest in this study. As a result, the study investigated the influence of transport operations on the changing local climate in Nigeria's southwestern cities. It investigated motorists' socioeconomic status (SES) and travel characteristics; the salient components of transport operations contributing to greenhouse gas emissions (GHG emissions); the effect of GHG emissions from transport operations on the local climate; transport externalities contributing to local temperature changes; and the effect of GHG emissions from transport operations on human health in the research location. This study employed a cross-sectional research design, utilizing systematic sampling to collect 580 copies of questionnaires administered to commercial motorists found in queues across two randomly selected parks in each capital city within the region. Both descriptive and inferential statistics (ANOVA and Linear Regression) were used to analyze the data. The study found that 60% of the motorists were middle-aged (aged between 36 and 45). The majority (70%) drive an average of 100 to 150 km, and premium motor spirit (PMS) is the primary source of energy for 95% of them. The nature and condition of the fuel in use are the top-ranked components of transport operations contributing to GHG emissions. The result of the ANOVA revealed a significant variation among the components of transport operations contributing to GHG emissions (F = 28.302, p = 0.000<0.05). Meanwhile, the linear regression results indicate that vehicular GHG emissions have a significant impact on the local climate (F1⁄578=30.091, p=0.000<0.05). Traffic congestion and bad road conditions were the top-ranked transport externalities contributing to the changing local climate. The most common effects of GHG emissions on human health were headaches and difficulty breathing. Considering these findings, this study suggests the best tactics to lessen the effects of GHG emissions from transport operations, which adversely affect the local climate and human health in the study area.